The genesis and consequences of stress among midwifery students - Khajehei, Marjan; Ziyadlou, S.; Hadzic, Maja; Kashefi, F. (MA Healthcare Limited, 2011)
This study investigated various sources of stress among junior and senior midwifery students in Iran. It also explored the effect of stress on the students’ performance and physical and mental health. Ninety junior and senior midwifery students participated in this survey. Data were collected using self-created questionnaires and analysed using the Statistical Package for the Social Sciences (SPSS). The data showed that the most stressful activity for juniors was nursing care practice. Prenatal health care practice was identified as the second most common cause of stress in juniors. For seniors, nursing care practice and prenatal health care practice were equally stressful. The preceptor (mentor) as well as the clinical setting and staff have been identified as two major factors causing stress, somewhat more in juniors than in seniors. The most common physiological and behavioural demonstrations of stress in the students were palpitation, exacerbated asthma, fatigue, unusual behaviour and dizziness. It is evident that efforts need to be made to minimize the negative effect of stress on students by creating and establishing healthy learning environments.